ASSESSMENT OF FINANCIAL PERFORMANCE IN SOE BANK USING THE DUPONT SYSTEM METHOD PERIOD 2019-2021 - Mar'atul Fitriyah H.; Abdi Akbar; Anwar; Anwar Ramli; Nurman (Transpublika Publisher, 2023)
Appraisal of a company's performance can be observed from both financial and non-financial perspectives. This study specifically measures financial performance by focusing on the DuPont System analysis. The DuPont system divides performance into three components: net profit margin, rate of return on assets, and rate of return on equity/capital. However, this study only considers two components of the DuPont System, namely return on assets and net profit margin. This research is of a quantitative nature with a descriptive approach. The data analyzed is derived from the financial statements of all state-owned banks, particularly the financial position statements and annual comprehensive income statements from December 31, 2019, to December 31, 2021. The results of the study indicate that, among the four banks, Bank Rakyat Indonesia (Persero) Tbk exhibits the best financial performance, while Bank Tabungan Negara (Persero) Tbk displays the lowest financial performance.